The Impact of Job Performance Due to Job Demands - Ramesh, Dr.C. (International Journal of Psychosocial Rehabilitation, 2020)
The main aim of this research is to know the impact of job performance due to job demands. An interview schedule was the main tool used to collect the data from the selected respondents. The statistical tools used for the research is ANOVA, Weighted Average Method, Rank and Discriminant analysis. At the end of the study it was found that the following job demand factors has affected their job performance they are Higher Authority s’ Misunderstanding of their personal problems, Lack of team spirit among colleagues, Personality clashes at work. Disturbances in their daily schedule and Dealing with angry students/customers/visitors.